PEMANFAATAN BAKTERI ENDOFIT UNTUK MENINGKATKAN KERAGAAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) - Fandi Hidayat; Suroso Rahutomo; Rana Farrasati; Iput Pradiko; Muhdan Syarovy; Edy Sigit Sutarta; Wiwik Eko Widayati (Jurnal Penelitian Kelapa Sawit, 2018)
Endophyte bacteria are microorganisms that live within plant tissue, harmless to the host plants, and usually contribute to plant health. Some of the endophytes are proved to be able to enhance plant growth by nitrogen fixation, phytohormones production such as indole acetic acid (IAA) and cytokines. This study aims to observe the influence of endophytic bacteria on the oil palm seedlings growth, nutrient absorption, and its potential on reducing the use of chemical fertilizer. The study was carried out in oil palm nursery at Aek Pancur substation since 3-monthsold until 9-monthsold. Treatments were arranged by using randomized completely block design (RCBD) with six treatments and repeated four times. The treatments are: (1) control; (2) 100% chemical fertilizer (standard); (3) 25% of urea dosage + inoculation of endophyte bacteria (B1N25); (4) 50% of urea dosage + inoculation of endophyte bacteria (B1N50); (5) 75% of urea dosage + inoculation of endophyte bacteria (B1N75); and (6) 100% of urea dosage + inoculation of endophyte bacteria (B1N100). The result showed that B1N75 was the best treatment indicated by higher relative agronomy effectiveness (RAE) up to 5.5% compared to standard. On the other hand, its growth and biomass production were also equal to standard treatment. It means that application of endophyte bacteria could reduce the use of inorganic nitrogen fertilizer (Urea) up to 25%.